Search for unknown neural link between the masticatory and cognitive brain systems to clarify the involvement of its impairment in the pathogenesis of Alzheimer’s disease - Kang, Youngnam; Toyoda, Hiroki; Saito, Mitsuru (Frontiers in Cellular Neuroscience, 2024)
Brain degenerations in sporadic Alzheimer's disease (AD) are observed earliest in the locus coeruleus (LC), a population of noradrenergic neurons, in which hyperphosphorylated tau protein expression and β-amyloid (Aβ) accumulation begin. Along with this, similar changes occur in the basal forebrain cholinergic neurons, such as the nucleus basalis of Meynert. Neuronal degeneration of the two neuronal nuclei leads to a decrease in neurotrophic factors such as brain-derived neurotrophic factor (BDNF) in the hippocampus and cerebral cortex, which results in the accumulation of Aβ and hyperphosphorylated tau protein and ultimately causes neuronal cell death in those cortices. On the other hand, a large number of epidemiological studies have shown that tooth loss or masticatory dysfunction is a risk factor for dementia including AD, and numerous studies using experimental animals have also shown that masticatory dysfunction causes brain degeneration in the basal forebrain, hippocampus, and cerebral cortex similar to those observed in human AD, and that learning and memory functions are impaired accordingly. However, it remains unclear how masticatory dysfunction can induce such brain degeneration similar to AD, and the neural mechanism linking the trigeminal nervous system responsible for mastication and the cognitive and memory brain system remains unknown. In this review paper, we provide clues to the search for such “missing link” by discussing the embryological, anatomical, and physiological relationship between LC and its laterally adjoining mesencephalic trigeminal nucleus which plays a central role in the masticatory functions.